LUMINOUS INTERCEPTION OF EUCALYPTUS CLONES AT DIFFERENT STRUCTURAL ARRANGEMENTS FOR INTEGRATED PRODUCTION SYSTEMS - Luz, Otávio dos Santos Limeira; Terra, Thiago Gledson Rios; Lima, Saulo de Oliveira; Siebeneichler, Susana Cristine; Moraes, Cristiano Bueno de; Leal, Tarcísio Castro Alves de Barros (Floresta, 2019)
Combinations of species, cultivars, clones and structural arrangements are cited as possibilities that may determine the interactions between these system components and management, needing to be better understood, especially in relation to shading capacity. In this sense, the present study aims to evaluate the light interception of Eucalyptus spp. clones at different structural arrangements for integrated production systems. An experiment was installed in randomized blocks design with five replications, in factorial scheme 4 x 2. Four structural arrangements A1 = Triple row (3,5 x 3,5 x 3,5) + 88 m; A2 = Double row (3,5 x 3,5) + 44 m; A3 = Single row 4 x 22 m; and A4 = Single row 4 x 11 m and two hybrids clones of Eucalyptus urophylla x E. grandis. For the estimation of the luminosity characteristics, the CI-110 imager equipment was used for estimate: the leaf area index, the average leaf angle, the coefficient of transmission, the sunflecks and the photosynthetically active radiation. Data were analyzed by variance analysis and the averages of the values of characteristics were compared by the Tukey test at 5% probability. The single row arrangement A4 promoted to the clones the greater shading capacity, characterized by high values of leaf area index, lower values of photosynthetically active radiation and by the densification of the arrangement of the other rows of alleys.